Perceptions, Expectations, and Informal Supports Influence Exercise Activity in Frail Older Adults. (7th April 2015) - Broderick, Louise; McCullagh, Ruth; Bantry White, Eleanor; Savage, Eileen; Timmons, Suzanne
This study aims to explore frail older adults' perceptions of what influences their exercise behaviors. A qualitative descriptive design was used. Semi-structured, open-ended interviews were conducted with 29 frail older adults. Thematic content analysis established the findings. Frail older adults perceive exercise as a by-product of other purposeful activities such as manual work or social activities. Progression into frailty appears to be associated with a decline in non-family support, changing traditional roles within family support networks, and lower baseline activity levels. Frail older adults perceive exercise as incidental to more purposeful activities rather than an endpoint in itself. Therefore, exercise programs concentrating on functional outcomes may be more relevant for this population. Strategies that educate and promote social support networks may also benefit frail older adults.